Mechanisms and Management of Retinopathy of Prematurity - Hartnett, M. Elizabeth; Penn, John S (The New England journal of medicine, 2012)
This article reviews retinopathy of prematurity, particularly regarding oxygen use, and describes current and potential therapies based on mechanistic studies in models relevant to current oxygen stresses in preterm infants. Retinopathy of prematurity is a vision-threatening disease associated with abnormal retinal vascular development that occurs only in premature infants. 1 Low birth weight and prematurity are strongly associated with an increased risk of the disease. 2 In the Early Treatment for Retinopathy of Prematurity study, the disorder developed in 68% of premature infants born in the United States and weighing less than 1251 g; among infants with the disorder, severe retinopathy of prematurity developed in almost 37%. 1 The incidence of premature births is increasing throughout the world, and with it, retinopathy of prematurity is now appearing in countries with the technology to . . .